2023
DOI: 10.1126/science.abq5622
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of STMN2 cryptic splice-polyadenylation and its correction for TDP-43 proteinopathies

Abstract: Loss of nuclear TDP-43 is a hallmark of neurodegeneration in TDP-43 proteinopathies, including amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). TDP-43 mislocalization results in cryptic splicing and polyadenylation of pre–messenger RNAs (pre-mRNAs) encoding stathmin-2 (also known as SCG10), a protein that is required for axonal regeneration. We found that TDP-43 binding to a GU-rich region sterically blocked recognition of the cryptic 3′ splice site in STMN2 pre-mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 80 publications
2
58
0
Order By: Relevance
“…TDP-43 deficiency has been linked to widespread cryptic splicing events, including but not limited to the splicing of STMN2, UNC13A, KALRN, RANBP1, and HDGFL2, eventually leading to neuronal dysfunction and death [1][2][3][4][5][6][7][8][9] . CLIP-seq data have revealed that TDP-43 predominantly binds to intronic GU repeats within pre-mRNAs 10 , where it sterically blocks the access of splicing factors to cryptic sites, resulting in the exclusion of cryptic exons from mature transcripts 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TDP-43 deficiency has been linked to widespread cryptic splicing events, including but not limited to the splicing of STMN2, UNC13A, KALRN, RANBP1, and HDGFL2, eventually leading to neuronal dysfunction and death [1][2][3][4][5][6][7][8][9] . CLIP-seq data have revealed that TDP-43 predominantly binds to intronic GU repeats within pre-mRNAs 10 , where it sterically blocks the access of splicing factors to cryptic sites, resulting in the exclusion of cryptic exons from mature transcripts 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, attention has been drawn to this mechanism of action for treating aberrant RNA splicing caused by TDP-43 deficiency. To date, research has primarily focused on correcting individual misspliced targets 11 . Although genes such as STMN2 and UNC13A have been shown to be important for neuronal health [1][2][3] , the downstream targets responsible for neuronal degeneration in TDP-43 pathology remain unknown, and it is possible that several targets act in concert.…”
Section: Introductionmentioning
confidence: 99%
“…similar to that reported for UNC13A 20,22 ) or co-regulation of mRNA targets by multiple RNA binding proteins (as has been previously demonstrated for TDP-43 and FMRP in Drosophila models 51,52 ) may be contributing factors. Nonetheless, this variability holds implications for future sALS focused clinical trials either targeting individual mRNA targets of TDP-43 themselves 19,23,27,28 or those seeking to utilize TDP-43 loss of function associated “cryptic” peptides or RNAs as biomarkers or readouts of therapeutic efficacy 21,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear depletion, and in some cells complete nuclear clearance, is thought to precede cytoplasmic mislocalization 17 and has been demonstrated to lead to a loss of nuclear function 1827 . Although early studies evaluated alterations in gene expression and mRNA splicing that occur in mice following TDP-43 depletion 24,26 , there is great dissimilarity between mouse and human TDP-43 targets due to a lack of conservation in the consensus sequence for TDP-43 binding in TDP-43 targets in mice 19,23,28 . To more accurately evaluate the role of TDP-43 nuclear depletion in human disease, recent studies utilized induced pluripotent stem cell (iPSC) technologies to identify alterations in gene expression and mRNA splicing that occur upon artificial depletion of TDP-43 in human neurons 19,20,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, cryptic splicing-polyadenylation of the stathmin-2 (STMN2) gene, encoding a protein required for axonal regeneration, is caused by TDP-43 mislocalization and is likely to be involved for axonal phenotypes and vulnerability of ALS MNs (Klim et al, 2019;Melamed et al, 2019). It is remarkable that ASOs targeted for TDP-43 binding sites within human STMN2 gene suppressed cryptic splicing, which restored axonal regeneration and STMN2-dependent lysosome trafficking in TDP-43-deficient human MNs (Baughn et al, 2023). This suggests the merit of ASO targeting STMN2 cryptic splicing for clinical application.…”
Section: Cryptic Rna Splicings Of the Targets Of Tdp-43mentioning
confidence: 99%